Outcomes of the International Seminar on Biofuels : policy choices facing developing countries (The Fund [Amsterdam]NL, 2008)
Deals with five matters that the Common Fund for Commodities should focus on in directing its assistance to biofuel-related projects viz. pro-poor orientation; biofuels and food security; the role of the private sector; the importance of technology transfer; and, the significance of pilot projects
Keywords: FUELS